2023
DOI: 10.1002/asia.202300050
|View full text |Cite
|
Sign up to set email alerts
|

Multichromophore Integrated Panchromatic Azaborondipyrromethenes: Synthesis, Characterization, and Exploring the Role of AzaBODIPY as an Energy and Electron Relay in Photoinduced Processes

Abstract: Panchromatic azaborondipyrromethenes directly connected with N,N‐ditolylaniline (TPA) and naphthalene (Naph) at 1,7‐ and/or 3,5‐positions of the azaBODIPY platform, 1, 2, and 3, were synthesized and the roles of the individual chromophore constituents in the photo‐induced energy and electron transfer processes have been investigated. Optical absorption studies have indicated that integrating the complementary absorbers, naphthalene and TPA moieties, into the azaBODIPY core yielded broad‐band capturing dyes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…This kind of NMR behaviour was also observed in naphthalene functionalized azaBODIPYs reported by our research group earlier. 92…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This kind of NMR behaviour was also observed in naphthalene functionalized azaBODIPYs reported by our research group earlier. 92…”
Section: Resultsmentioning
confidence: 99%
“…Compounds, 3 and Tolyl-azaBODIPY ( TABPY ) were synthesized according to the literature procedures. 92,95…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[43] These are in addition to studies reported by other groups. [44][45][46][47][48][49][50][51][52][53][54][55] In the present study, we report a new series of bisdonoracceptor push-pull systems featuring nitrogenous electron donors, viz., N,N-dimethylaniline (NND), triphenylamine (TPA), and phenothiazine (PTZ) with the help of acetylene linkers (see Figure 1 for structures along with those of the control compounds). Here, the azaBODIPY core is different from the traditionally used azaBODIPY in which two β-pyrrole-phenyl rings have been replaced with thiophene units and the αphenyl groups have acetenyl-phenyl entities.…”
Section: Introductionmentioning
confidence: 93%